2016
DOI: 10.1016/j.celrep.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Escape Mutation on T Cell and HIV-1 Co-adaptation

Abstract: The mechanistic basis for the progressive accumulation of Y(135)F Nef mutant viruses in the HIV-1-infected population remains poorly understood. Y(135)F viruses carry the 2F mutation within RW8 and RF10, which are two HLA-A(∗)24:02-restricted superimposed Nef epitopes recognized by distinct and adaptable CD8(+) T cell responses. We combined comprehensive analysis of the T cell receptor repertoire and cross-reactive potential of wild-type or 2F RW8- and RF10-specific CD8(+) T cells with peptide-MHC complex stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Within the vaccinated population, the HLA A * 02 genotype was a marker for success, with A * 02 + individuals showing significantly greater protection than A * 02 − individuals (54 vs. 3% effective). Other studies have made similar observations (237,238). These results not only illuminate the importance of making HLA-targeting considerations in the PBV design process, but also indicate how impactful MHC escape mutations can be when using PBVs to protect against AVPs (even when only one set of HLA-specific epitopes is affected).…”
Section: Pbv Targeting Strategies For Antigenically Variable Pathogensupporting
confidence: 66%
“…Within the vaccinated population, the HLA A * 02 genotype was a marker for success, with A * 02 + individuals showing significantly greater protection than A * 02 − individuals (54 vs. 3% effective). Other studies have made similar observations (237,238). These results not only illuminate the importance of making HLA-targeting considerations in the PBV design process, but also indicate how impactful MHC escape mutations can be when using PBVs to protect against AVPs (even when only one set of HLA-specific epitopes is affected).…”
Section: Pbv Targeting Strategies For Antigenically Variable Pathogensupporting
confidence: 66%
“…3 c). A previous study demonstrated that this mutation did not affect replication capacity [ 48 ]. These findings together suggest that the Y135F mutation may impair the suppression of HIV-1 replication by YF9-specific T cells, even though the mutation is not driven by HLA-B*35:01.…”
Section: Resultsmentioning
confidence: 99%
“…NL4-3 mutants (NL4-3YF9-1F) were previously generated by introducing the Nef YF9-1F mutation into NL4-3 using a site-directed mutagenesis system (Invitrogen, USA) [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies in HIV-1 have found HIV-1-specific CD8 T cells expressed these recombination [37,38], and the crystal structures of TCR-pMHC revealed that TRDV1/TRBV TCR was similar to the TRAV/TRBV structures [39]. Recently, several studies in HIV-1 have found HIV-1-specific CD8 T cells expressed these recombination [37,38], and the crystal structures of TCR-pMHC revealed that TRDV1/TRBV TCR was similar to the TRAV/TRBV structures [39].…”
Section: Discussionmentioning
confidence: 99%